Leadership in organizations - Yukl, Gary A., 1940- (Boston : Pearson, 2013)
The text that combines theory and practice to provide students with the skills they need for effective organizational leadership. See why scholars use this best seller as their primary source for finding out about topics in the field of leadership.
Introduction -- Nature of managerial work -- Effective leadership behavior -- Leading change and innovation -- Participative leadership and empowerment -- Leadership traits and skills -- Contingency theories and adaptive leadership -- Power and influence tactics -- Dyadic relations and followers -- Leadership in teams and decision groups -- Strategic leadership in organizations -- Charismatic and transformational leadership -- Ethical, servant, spiritual, and authentic leadership -- Cross-cultural leadership and diversity -- Developing leadership skills -- Overview and integration.
Includes bibliographical references and indexes.
Keywords: Leadership; Decision making; Organization